Fugitive Knowledge The Loss and Preservation of Knowledge in Cultural Contact Zones - Beer, Andreas; Mackenthun, Gesa (Waxmann, 2015)
Encounters between cultures are also encounters between knowledge systems. This volume brings together a number of case studies that explore how some knowledge in cultural contact zones becomes transient, evanescent, and ephemeral. The essays examine various aspects of cultural, especially colonial, epistemic exchanges, placing special emphasis on the fate of those knowledges that are not easily appropriated by or translated from one cultural sphere into another and thus remain at the margins of cross-cultural exchanges. In addition, the imposition of colonial power is unthinkable without the strategic deployment and use of knowledge; most colonial states, including those of Germany in the Baltic and in West Africa, were knowledge-acquiring machines - yet, acquisition always includes rejection, detainment and subjugation of recalcitrant epistemes. Bringing together insights from various scholarly disciplines, including literary studies, history, historical anthropology, and political science, the essays in this volume investigate how different or unfamiliar knowledge was, and in some cases still is, disarticulated by being belittled, discredited, and demonized. But they also show the strategies of resilience deployed by subjugated and subaltern people: the ways in which certain materials have escaped the coloniality of knowledge - how fragments and shards of other epistemologies remain inscribed in the polyphony and fuzziness of intercultural documents and archives.